Water governance and agricultural livelihoods: Navigating human-ecological systems and farmer strategies in Rural Zimbabwe - Mugambiwa, Shingirai (Edelweiss Applied Science and Technology, 2024)
Water plays an important role in agricultural livelihoods and it is increasingly significant in regions where precipitation is low and variability is high such as in semi-arid and arid regions. In such regions, there is a pressing need to manage, allocate, and utilize water resources wisely in order to enhance the sustainability of communities. This study aims to assess how water governance systems relate to farmers’ practices and rural livelihood in rural Zimbabwe with emphasis on Mutoko District, Mashonaland East. This was a qualitative exploratory study. Data was collected through semi-structured interviews, focus group discussions, and participant observations. The study consisted of a wide range of stakeholders including smallholder farmers, local authorities, and water management bodies. The study found that water resources management in rural Zimbabwe is a combination of both formal and informal processes. The study also revealed that effective implementation of policies has been deterred by lack of funding and political interference. It has also been established that to combat water shortage in the region, local farmers have engaged in growing drought-resistant varieties of crops, use of traditional water harvesting methods, and creating water conservation management associations. The paper concludes that there is a need to consider the human-ecological aspects, especially the influence of agriculture on the livelihoods of communities.